Analysis of the Legal Status of Fees/Ujroh in Multiservice Financing with Kafalah Agreements (Comparison of DSN-MUI Fatwa with AAOIFI) - Irham Maulana; Imron Rosyadi; Rizka (al-Afkar, Journal For Islamic Studies, 2024)
Since the introduction of Islamic banking in 1991, the Islamic economy has experienced significant growth. Many products and services have been introduced by sharia banks and other financial institutions to facilitate this need, with reference to various fatwas from the National Sharia Council - Indonesian Ulema Council (DSN-MUI). One of the services provided by sharia banking is multiservice financing, which is recognized as sharia valid through DSN-MUI Fatwa No: 44/DSN-MUI/VIII/2004. The focus of this research is on kafalah contracts, because DSN-MUI Fatwa No: 44/DSN-MUI/VIII/2004 allows multiservice financing using ijarah and kafalah contracts. Kafalah bil ujrah, as defined in the fatwa, is a guarantee transaction provided by a bank in exchange for wages. However, the legality of this contract is controversial because the arguments put forward by DSN-MUI are different from the standard arguments applied by AAOIFI, which actually prohibits it. Therefore, creative thinking is needed to find alternative contracts that can overcome this controversy and enable further developments in Islamic banking. The problem studied in this research is the concept of the kafalah contract according to the fatwa of the two institutions and the method of determining the fatwa (istinbath) of the two institutions regarding the kafalah contract. This research is library research with qualitative analysis. The method used is descriptive-comparative with the bayani, ta'lili and istislahi approaches.